Nondifferentiable Minimax Programming Problems in Complex Spaces Involving Generalized Convex Functions. (22nd December 2013) - Jayswal, Anurag; Prasad, Ashish Kumar; Kummari, Krishna
Abstract : We start our discussion with a class of nondifferentiable minimax programming problems in complex space and establish sufficient optimality conditions under generalized convexity assumptions. Furthermore, we derive weak, strong, and strict converse duality theorems for the two types of dual models in order to prove that the primal and dual problems will have no duality gap under the framework of generalized convexity for complex functions.